Quantification of soil losses using RUSLE model in the Boumlal watershed (Central Rif, Morocco) - El Ouazani Ech-Chahdi Khadija; El-Bouhali Abdelaziz; Amyay Mhamed (E3S Web of Conferences)
This contribution estimates soil losses in the Boumlal watershed by applying the Revised Universal Soil Loss Equation (RUSLE) and using GIS and remote sensing. This model incorporates five essential factors in water erosion: rainfall erosivity (R), soil erodibility (K), slope length (LS), cover management (C), and erosion control practice (P). The overlay of these parameters makes it possible to produce the synthetic map of annual soil losses (t/ha/year) and identify the most vulnerable areas to water erosion. The results indicate that Boumlal watershed is characterized by high sediment production. Indeed, more than 40% of the watershed produces a considerable amount of sediment exceeding 50 t/ha/year, with soil losses reaching over 200 t/ha/year in some parts of the study area. However, areas with low erosion rates represent approximately 33% of the total watershed area. The extent of water erosion and the high soil loss values are linked to the study area's vulnerability and inadequate anthropogenic interventions. Water erosion in this watershed directly affects soil quality, agricultural land productivity, arable land area, and the siltation of downstream reservoirs.